Modern Methods of Accelerating Orthodontic Tooth Movement in Delayed Eruption: a Systematic review - Doroshenko О. М.; Doroshenko М. В.; Omelianenko О. А. (Actual Dentistry, 2025)
Introduction. Delayed tooth eruption remains one of the most pressing problems in modern orthodontics, as it significantly complicates treatment planning and implementation, prolongs treatment duration, and increases the risk of complications. Patients with impacted teeth are more likely to experience gum recession, malocclusion, resorption of adjacent roots, and psychological discomfort, especially in adolescence. In this regard, the issue of accelerating orthodontic tooth movement in delayed eruption has gained particular relevance in both scientific and practical terms. Safety, biocompatibility, and proven effectiveness of the methods used are key criteria for choosing treatment tactics. A personalized approach, focusing on the condition of the bone tissue, type of retention, patient age, and concomitant pathologies, combined with interdisciplinary cooperation, is a key factor in determining success. Thus, in modern clinical orthodontics, the emphasis should be placed not only on eliminating mechanical obstacles to tooth eruption but also on actively stimulating the physiological processes of eruption to achieve rapid, stable, and aesthetically satisfactory results. Purpose: based on the analysis of literary sources, to evaluate the effectiveness of modern methods of accelerating orthodontic tooth movement in the case of delayed eruption. Materials and methods. Information search and analysis of scientific sources were conducted using the scientometric databases Web of Science, PubMed, and Google Scholar over the past 15 years. Conclusion: Modern methods of accelerating orthodontic tooth movement when their eruption is delayed allow to effectively shorten the duration of treatment and reduce the risk of complications, ensuring better clinical results thanks to a comprehensive and personalized approach.